Wall Building Inscriptions by the People of Apollonia from Leucas - Fiedler, Manuel; von Hesberg, Henner (Archäologischer Anzeiger, 2017)
Three identical inscriptions come from Leucas indicating that something was built by the people of Apollonia. The inscriptions can be assigned to the northern wing of the city wall. The wall was almost certainly rebuilt after its destruction by the Romans under L. Flaminius in the years following the siege of 197 B.C. The forms of the letters and general considerations of the history of the city confirm a dating to this period. The inscriptions clearly and visibly show that the people of Apollonia – certainly Apollonia on the Adriatic – intended to help Leucas. This intent to support was motivated by the common interests of two traditional and independent poleis in this part of the Adriatic and Ionian Sea, but it was probably also reinforced in the still-vaunted community with Corinth. Both cities had been founded from there in the Archaic period.